PROFESSIONAL LANGUAGE TRAINING OF INTERNATIONAL RELATIONS STUDENTS - Victor B. Kirillov; Elena V. Voevoda (Высшее образование в России)
The article considers the key points of professional language training of IR students. The authors analyze the interrelated conditions that determine its effectiveness: building professionally relevant competences, specifics of professional language training,cross-cultural awareness, the use of educational technologies as well as selection of teaching materials and re-training lecturers.